2020
DOI: 10.1038/s41467-020-14734-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise enhances skeletal muscle regeneration by promoting senescence in fibro-adipogenic progenitors

Abstract: Idiopathic inflammatory myopathies cause progressive muscle weakness and degeneration. Since high-dose glucocorticoids might not lead to full recovery of muscle function, physical exercise is also an important intervention, but some exercises exacerbate chronic inflammation and muscle fibrosis. It is unknown how physical exercise can have both beneficial and detrimental effects in chronic myopathy. Here we show that senescence of fibro-adipogenic progenitors (FAPs) in response to exercise-induced muscle damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 70 publications
(92 reference statements)
5
100
0
Order By: Relevance
“…Moreover, long‐term forced treadmill running showed contradictory effects on the markers of senescent cells, including p16 INK4a , p21 Cip1 , and SA‐β‐Gal (Bao et al, 2020; Jang et al, 2019; Wong et al, 2019; Yoon et al, 2019; Zhang et al, 2016), although four out of five studies showed senolytic effects of exercise in specific tissues under obesity or aging conditions. Conversely, studies on an acute bout of downhill running and prolonged swimming reported an increased level of p21 Cip1 and SA‐β‐Gal in fibro/adipogenic progenitors (Saito et al, 2020), and liver and brain (Huang et al, 2013; Liu et al, 2019), respectively, while another swimming study indicated a reduced level of SA‐β‐Gal in the muscle (Fan et al, 2017). In summary, 10 out of 13 animal studies showed a senolytic effect of exercise, but this effect was influenced by the form and dosage of exercise, type of senescent tissue or cells, and healthy or aging/disease conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, long‐term forced treadmill running showed contradictory effects on the markers of senescent cells, including p16 INK4a , p21 Cip1 , and SA‐β‐Gal (Bao et al, 2020; Jang et al, 2019; Wong et al, 2019; Yoon et al, 2019; Zhang et al, 2016), although four out of five studies showed senolytic effects of exercise in specific tissues under obesity or aging conditions. Conversely, studies on an acute bout of downhill running and prolonged swimming reported an increased level of p21 Cip1 and SA‐β‐Gal in fibro/adipogenic progenitors (Saito et al, 2020), and liver and brain (Huang et al, 2013; Liu et al, 2019), respectively, while another swimming study indicated a reduced level of SA‐β‐Gal in the muscle (Fan et al, 2017). In summary, 10 out of 13 animal studies showed a senolytic effect of exercise, but this effect was influenced by the form and dosage of exercise, type of senescent tissue or cells, and healthy or aging/disease conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 16 out of 21 articles were included in the meta‐analysis. However, two studies were excluded because of a lack of essential data (Wu et al, 2019; Zhang et al, 2016), one studies were excluded because of less than two data with similar outcomes and design (Saito et al, 2020), one study was excluded because the data were taken from cohort reported in another study (Tsygankov et al, 2009), and one study was excluded because of the fact that exercise was not an independent factor (Yang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A higher percentage of DNA‐damaged satellite cells could influence the ability of muscle to adapt and regenerate. However, given that a recent report showed that senescent cells, specifically fibro‐adipogenic progenitor cells, are actually required for muscle regeneration, 74 the relative impact, if any, of satellite cell abundance compared to the percentage that are senescent on muscle mass loss with age remains to be determined. Overall, our results show that γH2AX+ satellite cells are rare in resting muscle in vivo (1 per every 200 myofibers) regardless of age.…”
Section: Discussionmentioning
confidence: 99%
“…Other senescent cells, termed here helper-(H-) senescent cells, do not appear to release inflammatory and pro-apoptotic factors substantially and may be involved in promoting stem and progenitor cell determination into appropriate lineages and functions [43,44] (unpublished observations). Hsenescent cells might account for 30 to 70% of senescent cells.…”
Section: Cellular Senescencementioning
confidence: 99%